PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI (Studi Pada BNI KCU UNDIP SEMARANG) - Pangstu, Anita Ayu; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2014)
Work satisfaction and organizational commitment influence staff performance . The purpose of this research to explain how the variable of work satisfaction and organizational commitment influence to BNI KCU Undip Semarang staffs. In addition on it is use to recognize which variable influences dominantly to the performanceThe data of this research are obtained by giving the quistionare to the 32 BNI KCU Undip Semarang staffs . The data tes tecnique in this research are istrument test ( realibility test , validity test ), clasical asumption test ( normality test , heterosekdesitas test, linearity test , multilinear regression analysis , T-test , F-test , Coefisient of determination test using SPSS 20.0 aplication .The result shows that the work satisfaction and organizasional commitment influence positively and significantly to the staff performace, variables used in this research give positive responce , meaning the work satisfaction and organizational commitment improving the performance BNI KCU Undip Staff. Value of determination coefisien or R square is 0,663, which means staff performance is affected by staff satisfication and organizational commitment as 66,3%.